Pendidikan Politik: Konsep Nilai Etika Universal Perspektif Kohlberg Dan Islam - Suryawan, Muhammad Hasan (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The emerge of unlimited, transparency, globally type of new media creates a lot of dynamics. It plays important role in the socialization process of political well as being a government media that accumuleate some aspiration and provide the peoples. In addition, the unlimited media has been used several group carry out political hegemony that bringout conflict among sympathizer. With the result that obscure the purpuse of politic to achieve global public goodness. So that, moral re-formulation in politics are required an alternative way to cultivate the right of moral education. One of them is the revolutionary concept of Kohlberg about the importance of moral universal in the character. Islam have also universal ethics which is the subject matter as its mission as a religion of mercy for the universe. Ethics is in line with the universal values of humanity, equality, justice and human rights. And then eventually, the formation of inclusive characters will affects moral in politics. Munculnya jenis media baru yang tidak terbatas, transparan, global dan bebas menimbulkan banyak dinamika. Ia berperan penting dalam proses sosialisasi politik sekaligus menjadi media pemerintah dalam mengumpulkan aspirasi dan layanan bagi masyarakat. Selain itu ketidakterbatasan media tersebut telah digunakan kelompok lain dalam melakukan hegemoni politik yang pada akhirnya memunculkan konflik pada kalangan simpatisannya sehingga mengaburkan tujuan berpolitik untuk meraih kebaikan bersama. Untuk itu perumusaan kembali moral berpolitik memerlukan jalan alternatif dalam membudayakan pendidikan moral yang tepat. Salah satunya ialah dengan konsep revolusioner Kohlberg tentang pentingnya moral universal dalam karakter. Dalam islam terdapat nilai etika universal yang menjadi pokok ajaran sebagaimana misinya bahwa agama pembawa rahmat bagi alam semesta. Etika itu bersesuaian dengan nilainilai universal kemanusiaan, kesetaraan, keadilan dan hak asasi manusia. Pada akhirnya terbentuknya karakter inklusif tersebut akan mempengaruhi moral dalam berpolitik.